2020
DOI: 10.1108/jocm-11-2019-0327
|View full text |Cite
|
Sign up to set email alerts
|

Exploring role of Indian workplace spirituality in stress management: a study of oil and gas industry

Abstract: PurposeThe primary objective of the present study is to explore the relationship between workplace spirituality and work stress among offshore and onshore employees of the Indian oil and gas industry. The present study also tends to study the difference in the stress level of offshore and onshore employees of the Oil and Gas Industry.Design/methodology/approachThe size of the sample for the present study was 202 respondents. It includes 128 onshore employees and 74 offshore employees of oil and gas companies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 97 publications
(104 reference statements)
2
45
0
Order By: Relevance
“…Subramani and Kadhiravan (2017) had established how the student finds it difficult to deal with the academic stressors and they are unable to find ways to deal with them. Academic failure and dissatisfaction with life can also lead to other forms of deviant behaviors (Saxena et al,2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subramani and Kadhiravan (2017) had established how the student finds it difficult to deal with the academic stressors and they are unable to find ways to deal with them. Academic failure and dissatisfaction with life can also lead to other forms of deviant behaviors (Saxena et al,2020).…”
Section: Discussionmentioning
confidence: 99%
“…It fills the student with negative emotions and subsequently, an unknown fear of failure surrounds the student. Several researchers, including Saxena et al (2020), reported that excessive stressful adolescent students are more prone to indulge in alcoholism and drug abuse. Few other undesirable repercussions of stressed academic life are physical and mental inactivity, dullness, eating and sleeping habit disorder and unprotected and failed sexual life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study's overarching idea is that individual spirituality is an essential tool to encourage nonviolent work behavior. Thirdly, it has been argued that most of the reviews, such as Garg (2017b), and Saxena, Garg, Punia, and Prasad (2020), have explored organizational outcomes of either individual spirituality or workplace spirituality alone. This is one of the few studies that empirically establish a multilevel model of spirituality and organizational outputs.…”
Section: Theoretical Implications Of the Studymentioning
confidence: 99%
“…Sources of work stress can also come from physical and physical threats and violence at work (Allison et al, 2019;Rasool et al, 2020), financial problems (Kongcharoen et al, 2019), delays in information (Ajayi et al, 2019), the use of digital technology (Rafida, 2020), countermeasures, resilience extraversion, awareness and neuroticism (Duschek et al, 2019), personal relationships outside of work and lack of free time for family and friends (Galanis et al, 2018), customer misbehaviors (Hu et al, 2017), customer abusive behaviour (Kashif et al, 2017) psychological empowerment (Tripathi and Bharadwaja, 2018) and spirituality at work (Saxena et al, 2020). Some of the antecedent variables of work stress have never been studied in previous studies, thus adding to the research literature on work stress.…”
Section: Antecedents Of Work Stressmentioning
confidence: 99%